Acute gynecological diseases in urgent surgical practice - К. S. Dolim; А. Sh. Аbdumazhidov; Z. Z. Тukhtamurod (Клінічна хірургія)
Objective. To analyze the cases of admittance of the patients, suffering an acute gynecological diseases, into Urgent Surgical Department.